The role of deubiquitinases in cardiovascular diseases: mechanisms and therapeutic implications - Fei, Xiangyu; Song, Chao; Cui, Jian; Li, Yuqing; Lei, Xiaoyong; Tang, Huifang (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVDs) have become the leading cause of death globally, surpassing infectious diseases and other chronic illnesses. The incidence and mortality rates of CVDs are rising worldwide, posing a key challenge in public health. The ubiquitination system is a vast and complex. It is an important post-translational modification that plays a crucial role in various cellular processes. Deubiquitination is catalyzed by deubiquitinases (DUBs), which remove ubiquitin (Ub) from ubiquitinated proteins, thereby reversing the ubiquitination process. DUBs play an important role in many biological processes, such as DNA repair, cell metabolism, differentiation, epigenetic regulation, and protein stability control. They also participate in the regulation of many signaling pathways associated with the development and progression of CVDs. In this review, we primarily focus on the role of DUBs in various key pathological mechanisms of atherosclerosis (AS), such as foam cell formation, vascular remodeling (VR), endothelial-to-mesenchymal transition (End-MT), and clonal hematopoiesis (CH). In the heart, we summarize the involvement of DUBs in diseases and pathological processes, including heart failure (HF), myocardial infarction (MI), myocardial hypertrophy (MH) and ischemia/reperfusion (I/R) injury. Additionally, we also explore the diabetic cardiomyopathy (DCM) and the use of doxorubicin-induced cardiotoxicity in clinical settings. A comprehensive understanding of deubiquitination may provide new insights for the treatment and drug design of CVDs.